Estudo de propriedades reológicas de emulsões de petróleo água/óleo - Fiorotti, Thiago Amorim (2016)
Water-in-Oil emulsions constitute an operational problemin the petroleum industry. Among then,is highlight the variation in the rheological properties of this matrix when compared to the dehydrated oil. The transverse relaxation time (T2) obtained by low field NMR wasused to determine the pseudoplasticity (n) and consistency index(k) of emulsions containing different percentage of disperse phase.In this study, 90 emulsions from 10 samples of oil with ° API ranging from18.7 to 28.3 were used. Depending of the amount of emulsified water, there is an increase of approximately 400% in the apparent viscosity and a more evidenced pseudoplastic behavior. From the results it was proposed a model to calculate the kand nvalues from only one measure of T2. To validate the model, emulsions of five different oils were used, yielding very satisfactory results for the NMR prediction of viscosity in the range of 100 to 600 mPa.s. Finally, low field NMR is a good alternative to ASTMD2196-15 method that is commonly used to measure the dynamic viscosity